Simultaneous bilateral spontaneous pneumothorax in an adult patient with cystic fibrosis Pneumotórax espontâneo simultâneo bilateral em um paciente adulto com fibrose cística - Kamlesh Mohan (Jornal Brasileiro de Pneumologia, 2009)
Pneumothorax is a common complication in cystic fibrosis and is associated with worsening of lung function. However, bilateral simultaneous pneumothorax in cystic fibrosis is a rare condition. We describe the case of a 17-year-old female with cystic fibrosis who presented with spontaneous pneumothorax. Clinically, she presented right-sided chest pain and progressive breathlessness. The pneumothorax failed to resolve after the initial treatment (chest drainage). However, the patient was later successfully treated with additional chest drainage and talc pleurodesis. We also discuss the etiology and management of pneumothorax in patients with cystic fibrosis, since pneumothorax is associated with increased morbidity and mortality among such patients. O pneumotórax é uma complicação comum na fibrose cística e está associado com a piora da função pulmonar. Entretanto, o pneumotórax simultâneo bilateral na fibrose cística é um achado raro. Nesse artigo é descrito o caso de uma paciente de 17 anos com fibrose cística que cursou com pneumotórax espontâneo simultâneo bilateral. Clinicamente ela apresentou dor torácica à direita e dificuldade respiratória progressiva. Embora o pneumotórax não tenha respondido bem ao tratamento inicial (drenagem torácica), ela foi posteriormente tratada com drenagem e pleurodese com talco, com sucesso. São discutidos também a etiologia e a conduta nesta condição, que está associada com o aumento da morbidade e mortalidade.